1977
DOI: 10.1136/adc.52.9.716
|View full text |Cite
|
Sign up to set email alerts
|

Circulating thyroid hormone levels in children

Abstract: SUMMARY Extensive use of radioimmunoassay for routine measurement of serum thyroid hormones in paediatric thyroid disorders showed inconsistencies between laboratory results based upon adult criteria and clinical observation. To resolve this disparity, serum triiodothyronine (T3) and thyroxine (T4) levels were measured by radioimmunoassay in 354 healthy children aged between 3 weeks and 1 7 years.The mean serum T3 concentration in children up to 10 years of age was 1 94±0*35 ng/ml (SD) which was higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…Similarly, in several species of terrestrial mammals, thyroid hormone concentrations appear to be higher in younger than older dogs (Reimer et al 1990), cats (Skinner, 1998), and goats (Colavita et al, 1983). Although the basis for the age-related effects of thyroid hormones in managed care dolphins is not known, it is well known that thyroid hormones support early childhood development and maturation in humans (Corcoran et al, 1977;Croughs et al, 1965) and appear to be necessary for adapting to extreme or changing environmental conditions as found in wild pinniped pups and other wild marine mammals (Engelhardt and Ferguson, 1980;Fair et al, 2011;Haulena et al, 1998;Porterfield and Stein, 1994;Stokkan et al, 1995;Woldstad and Jenssen, 1999). Nonetheless, the present results combined with previous results in wild dolphins and other mammalian species provides support for an age-related (juvenile to adult) decrease in thyroid hormone concentrations in female and male bottlenose dolphins.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in several species of terrestrial mammals, thyroid hormone concentrations appear to be higher in younger than older dogs (Reimer et al 1990), cats (Skinner, 1998), and goats (Colavita et al, 1983). Although the basis for the age-related effects of thyroid hormones in managed care dolphins is not known, it is well known that thyroid hormones support early childhood development and maturation in humans (Corcoran et al, 1977;Croughs et al, 1965) and appear to be necessary for adapting to extreme or changing environmental conditions as found in wild pinniped pups and other wild marine mammals (Engelhardt and Ferguson, 1980;Fair et al, 2011;Haulena et al, 1998;Porterfield and Stein, 1994;Stokkan et al, 1995;Woldstad and Jenssen, 1999). Nonetheless, the present results combined with previous results in wild dolphins and other mammalian species provides support for an age-related (juvenile to adult) decrease in thyroid hormone concentrations in female and male bottlenose dolphins.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported changes in total thyroid hormone and binding protein level during childhood (4)(5)(6), but it is likely that changes in the free hormone concentrations of T3 and T4 are more pertinent to normal growth and develop¬ ment. Some investigators have extrapolated free hormone concentrations from total thyroid hor¬ mone and binding protein levels (7,8), but the more recent direct methods of free hormone measure¬ ment have only been applied in one study reported by Butler et al (9).…”
mentioning
confidence: 97%
“…While there is general agreement that circulating levels of thyroid hormones decline throughout adolescence (25,26), the relationship between thyroid status and pubertal development is not clear. Corcoran and colleagues (27) reported that there was a peripubertal nadir in circulating levels of thyroid hormones in children, although it occurred 2 years later in boys than in girls. In another crosssectional study in children in which data from boys and girls were combined, there was a transient increase in thyrotropin secretion and a resultant rise in T4 and tri-iodothyronine (T3) that preceded clinical pubertal changes (28).…”
Section: Introductionmentioning
confidence: 99%